The Role of Our National Values in Shaping The Culture of Behavior in Preschool Children - kizi, Ganieva Dilnoza Urol (European Journal of Life Safety and Stability (2660-9630), 2022)
This article confirms the proposals and conclusions, such as the role of national values in the formation of behavioral culture in preschool children and the development of criteria for the education of behavior in preschool children through national values.